2007
DOI: 10.1002/pon.1308
|View full text |Cite
|
Sign up to set email alerts
|

The effect of group cohesion on rehabilitation outcome in cancer survivors

Abstract: The effect of group cohesion on rehabilitation outcome in cancer survivors May, Anne M.; Duivenvoorden, Hugo J.; Korstjens, Irene; van Weert, Ellen; HoekstraWeebers, Josette E. H. M.; van den Borne, Bart; Mesters, Ilse; van der Schans, Cees P.; Ros, Wynand J. G. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…Synonymous with previous research, the high social identity scores revealed the possibility of AHT providing a strong supportive care network that promotes a positive cancer identity through group membership [29,30]. The common denominators of breast cancer and motorcycles provided participants with an initial shared connection, through which participants could develop deeper relationships with individuals and with the AHT group as a whole.…”
Section: Strengths and Limitationsmentioning
confidence: 60%
See 1 more Smart Citation
“…Synonymous with previous research, the high social identity scores revealed the possibility of AHT providing a strong supportive care network that promotes a positive cancer identity through group membership [29,30]. The common denominators of breast cancer and motorcycles provided participants with an initial shared connection, through which participants could develop deeper relationships with individuals and with the AHT group as a whole.…”
Section: Strengths and Limitationsmentioning
confidence: 60%
“…To date, there have been no studies directly linking social identity or group cohesion with PTG. However, studies have highlighted that identifying with a group and the bond created within that group is linked with an improved quality of life in cancer survivors participating in exercise interventions [e.g., 29,30]. Midtgaard et al [30] showed that although the initial link to the exercise group was their cancer, a shift in participants' cognitions and behaviour occurred during the exercise intervention.…”
Section: Social Identity Through Group Membershipmentioning
confidence: 97%
“…However, group-based physical training interventions have been shown to be effective in increasing cancer survivors' HRQOL. 39 This probably reflects the psychosocial benefits that can accrue when group cohesion is created, providing social support and positive social comparisons. Additionally, cancer patients and survivors indicate that exercising in groups can increase one's motivation to overcome their physical limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Physically active prostate cancer patients also have significantly lower serum insulin and insulin-like growth factor (IGF-1), higher insulin-like growth factor binding protein (IGFBP-1) and a lower risk of high grade disease (Gleason score 7 or greater) compared to less-active prostate cancer patients [38][39][40] . Exercise is relatively inexpensive compared to pharmacological and/or radiation approaches 1 and has a social aspect that is important for older adults 41,42 and those with cancer 43,44 .…”
Section: Insert Figurementioning
confidence: 99%